PERAN PEMERINTAH DALAM PENANGGULANGAN HIV DAN AIDS - Ngadnan, Ngadnan (Jurnal Kebijakan Publik, 2016)
Role of Government in Response to HIV and AIDS. This study aims to analyze the role ofthe city government Tanjungpinang in HIV and AIDS in 2014 based on the conceptual Ndraha andKovner and analyze bottlenecks in implementation. Mentioned in Ndraha role of local governmentsinclude three things: service, empowerment and development. Conceptual Kovner explains the roleof government in the health sector as donors, implementers and regulatory activities. The studywas conducted from March to May 2016 in the city of Tanjungpinang of Riau Islands province.This research method is descriptive qualitative approach. Informants were selected purposively iepeople who are considered to have knowledge of and involved in the implementation of HIV andAIDS in the government of the city of Tanjungpinang. The research data were obtained based onthe in-depth interviews. The results showed that the government’s role Tanjungpinang in HIV andAIDS in 2014 have been implemented although implementation is not optimal. Obstacles in theimplementation process is still a lack of synergy and coordination between stakeholders, are notyet available regulatory areas of the city that regulates the response to HIV and AIDS, includingadequate funding and guarantee the sustainability of HIV and AIDS programs in the future.